Subcutaneous Recurrences of Thyroid Cancer After Conventional Transcervical Thyroidectomy: A Case Report - Dong, Xubin; Lv, Shihui; Zhang, Xiaohua; Li, Quan (Frontiers in Surgery, 2020)
Metastatic subcutaneous implantation of the follicular variant of papillary thyroid cancer is very rare. We present a 62-year-old woman with a history of follicular variant of papillary thyroid cancer, who developed multiple asymptomatic subcutaneous nodules, after 5 years of initial thyroidectomy. Eventually, the subcutaneous nodules were diagnosed as tumor recurrence and completely excised. She has reportedly lived for more than 1 year, without signs of disease progression or recurrence. This case emphasizes the need for surgeons to take into account the tumor-free concept during the operation, and to a great extent prevent the occurrence of implantation recurrence.